PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN PADA PT BANK INDONESIA SYARIAH Tbk AREA JAKARTA THAMRIN - Sofyanti, Hizbillah Atqiya; Ananto, Tri (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
This research is entitled "the effect of training and work environment on employee performance at PT Bank Syariah Indonesia Tbk Jakarta Thamrin Area". The purpose of this study is to determine the effect of Training and Work Environment on the Performance of Employees of PT Bank Syariah Indonesia Tbk Jakarta Thamrin Area. With Training and Work Environment as independent variables and Employee Performance as dependent variables. This study used quantitative research design with associative methods. Data collection was carried out by distributing questionnaires to all employees of PT Bank Syariah Indonesia Tbk Jakarta Thamrin Area as many as 68 respondents. The sampling technique is purposive sampling. Processing the data in this study using SPSS 25. The results of this study show that the Training variable has a positive and significant influence on Employee Performance, the Work Environment variable has a positive and significant influence on Employee Performance and in the simultaneous test there are results that the Training and Work Environment variables together have a positive and significant effect on Employee Performance of PT Bank Syariah Indonesia Tbk Jakarta Thamrin Area.Keywords: Training, Work Environment, and Employee Performance Discipline.